2023
DOI: 10.3390/separations10080458
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cumin (Cuminum cyminum) Incorporation on the Generation of Heterocyclic Aromatic Amines in Meatballs

Elif Ekiz,
Adem Savaş,
Eyad Aoudeh
et al.

Abstract: In the current study, the impacts of using cumin (0.5% and 1%, w/w) in beef meatballs on heterocyclic aromatic amines (HAAs) formation and some quality characteristics when cooked at 150 and 250 °C were investigated. It was found that using of cumin at different ratios in beef meatballs showed a significant (p < 0.01) effect on pH, thiobarbituric acid reactive (TBARS) value, and total HAA. The cooking process significantly (p < 0.01) affected the meatballs’ water content, pH, and TBARS values, while the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 69 publications
(146 reference statements)
3
2
0
Order By: Relevance
“…While a positive correlation was observed between total HAA levels and protein ( r = 0.58, P < 0.01), fat ( r = 0.5, P < 0.01), and cooking loss ( r = 0.47, P < 0.01), a negative correlation was found between total HAA levels and water ( r = −0.35, P < 0.05). The current findings align with previous reports, 37,57 underscoring the adverse association between water and HAA formation, as water facilitates the transportation of precursors to the meat surface. Furthermore, the positive correlation between cooking loss and total HAAs might be linked to the transport of water‐soluble precursors to the meat's surface.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…While a positive correlation was observed between total HAA levels and protein ( r = 0.58, P < 0.01), fat ( r = 0.5, P < 0.01), and cooking loss ( r = 0.47, P < 0.01), a negative correlation was found between total HAA levels and water ( r = −0.35, P < 0.05). The current findings align with previous reports, 37,57 underscoring the adverse association between water and HAA formation, as water facilitates the transportation of precursors to the meat surface. Furthermore, the positive correlation between cooking loss and total HAAs might be linked to the transport of water‐soluble precursors to the meat's surface.…”
Section: Resultssupporting
confidence: 92%
“…Similarly, in a prior study, when basil extract was applied to the beef samples cooked on a grill at 200 °C for 20 min, it resulted in an elevation of PhIP content compared to the control samples, and this increase was attributed to the prooxidant effects of the basil extract 48 . In accordance, another previous research revealed that addition of 0.5% and 1% cumin increased the formation of PhIP in meatballs cooked at 250 °C 37 . Research has revealed that the formation of PhIP results from the Maillard reaction, which involves glucose, phenylalanine, and creatine 49 .…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations